Answer:
52.095 m/s
Motorcycle a was moving faster
Explanation:
We start by using one of the equations of motion
V = u + at
If the first motorcycle starts with an initial speed of u(a) and accelerates at a value of a(a) = 4.55 m/s², then the final speed after a time of 3.63 seconds is V(a). We then represent it as
V(a) = u(a) + a(a).t
If the second motorcycle starts with an initial speed of u(b) and accelerates at a value of a(b) = 18.9 m/s², then the final speed after a time of 3.63 seconds is V(b). We then represent it as
V(b) = u(b) + a(b).t
Assuming that the final speeds v(a) = v(b), and then subtract the equation of the second motorcycle from that of the first, we have
0 = u(a) - u(b) + a(a).t - a(b).t
-u(a) + u(b) = a(a).t - a(b).t, on rearranging, we have
u(b) - u(a) = [a(a) - a(b)]t
Since we have the values for acceleration and the time, we substitute so that
u(b) - u(a) = (4.55 - 18.9)3.63
u(b) - u(a) = -14.35 * 3.63
u(b) - u(a) = -52.095, or we rearrange to get
u(a) - u(b) = 52.095 m/s